Avaliação do efeito da radiação gama na qualidade do mamão (Carica papaya L.): características nutricionais, textura, parâmetros de estresse oxidativo e genéticos - Silva, Geralda Gillian (2008)
The gamma irradiation process is an important strategy to post-harvest conservation and fruit’s commercialization. This work had as an objective to evaluate the effect of gamma radiation in the nutritional characteristics, texture and on the stress oxidative and genetic parameters of papaya fruit (Carica papaya L.) of the ‘Solo’ Golden group. Irradiated fruits (0.8 kGy - cobalt-60 source) were evaluated as the water contents, fibers, ash, totals lipids, proteins, carbohydrates, carotenoids and vitamin C (at the 5, 7 and 9th day post-harvest (dph)); at the texture; activity of the catalase - CAT and peroxidase – POX enzymes; lipid peroxidation and possible damages to the genetic material (during its shelf life). The radiation dose applicated did not alter the content of water, ash, proteins and as of lycopene, as did not carry mutagenicity and genotoxicity in the fruits. However, the irradiated fruits presented higher content of fibers and lower content of lipids and vitamin C; content a little bit of carbohydrates (5th th dph) and total carotenoids (7 dph) when compared to the controls fruits and an increase of lipid peroxidation, the one what can suggest an inducement of oxidative stress. The irradiation altered the profile of CAT and POX activities, which that can be related to the higher firmness and a lower content of carbohydrates of the irradiated fruits, which indicates that the irradiation delayed ripening of the fruits. The results demonstrated that the gamma irradiation (0.8 KGy) do not change the papaya quality, being a process promissory in the conservation post harvest of these fruits.